Disability and the criminal justice system in Zambia. Issue 2 (12th June 2017) - Jacobson, Jessica; Sabuni, Phillip; Talbot, Jenny
Abstract : Purpose: Drawing on multi-method research conducted in 2013-2014, the purpose of this paper is to consider the extent and nature of disadvantage experienced by individuals with psychosocial and intellectual disabilities (PID) who come into contact with the criminal justice system in Zambia. The research was conducted as part of a wider project aiming to bring about improvements in how people with PID are dealt with by the criminal justice services. Design/methodology/approach: The research activities included interviews with 29 individuals with PID who had experienced the criminal justice system as suspects, defendants or prisoners ("self-advocates"). A focus group and interviews were also conducted with the family members of people with PID who had criminal justice experience. Findings: People with PID in contact with the criminal justice services in Zambia are disadvantaged and discriminated against routinely and systematically. Like all detainees, they experience harsh and at times brutal conditions of detention. However, because of their disabilities, such experiences can be more keenly felt: their disabilities may be exacerbated by detention or by limited or non-existent health care; and they are likely to be less resourceful than other detainees and, therefore, less able to cope with the privations of detention. Originality/value: In drawing on the self-advocate interviews, this paper presents direct, vivid accounts of what it means to be a suspect, defendant or prisoner with disabilities in Zambia. These are extremely marginalised and multiply disadvantaged individuals whose voices are rarely heard.